Kinerja Lingkungan Industri Kecil Agro di Priangan Timur - Charina, Anne; Kusumo, Rani Andriani Budi; Mukti, Gema Wibawa (Universitas Galuh, 2024)
With increasing global demands to contribute to a sustainable world, small industries are starting to express awareness of the importance of environmental safety and health in their businesses. This research aims to explore the environmental performance of agri-small industries in East Priangan using a qualitative approach. Interviews were conducted with 10 small agro industry owners who adopted environmental practices in their business. Thematic analysis with N-vivo version 12 software was used to analyze the data obtained. This research reveals that business owners' knowledge of the importance of environmental safety is the basic motive behind the environmental performance of small agro industries. The types of environmental performance that are carried out by many agri-small industries in East Priangan include: simple waste processing, use of safe raw materials and certification and standardization for food products. The cost component is something that needs to be considered, because it often becomes an obstacle in implementing environmental performance in agri-small industries.